A modeling study of coastal circulation and landfast ice in the nearshore Beaufort and Chukchi seas using CIOM. Issue 6 (4th June 2014) - Wang, Jia; Mizobata, Kohei; Bai, Xuezhi; Hu, Haoguo; Jin, Meibing; Yu, Yanling; Ikeda, Moto; Johnson, Walter; Perie, William; Fujisaki, Ayumi
Abstract This study investigates sea ice and ocean circulation using a 3‐D, 3.8 km CIOM (Coupled Ice‐Ocean Model) under daily atmospheric forcing for the period 1990–2008. The CIOM was validated using both in situ observations and satellite measurements. The CIOM successfully reproduces some observed dynamical processes in the region, including the Bering‐inflow‐originated coastal current that splits into three branches: Alaska Coastal Water (ACW), Central Channel branch, and Herald Valley branch. In addition, the Beaufort Slope Current (BSC), the Beaufort Gyre, the East Siberian Current (ESC), mesoscale eddies, and seasonal landfast ice are well simulated. The CIOM also reproduces reasonable interannual variability in sea ice, such as landfast ice, and anomalous open water (less sea ice) during the positive Dipole Anomaly (DA) years, vice versa during the negative DA years. Sensitivity experiments were conducted with regard to the impacts of the Bering Strait inflow (heat transport), onshore wind stress, and sea ice advection on sea ice change, in particular on the landfast ice. It is found that coastal landfast ice is controlled by the following processes: wind forcing, Bering Strait inflow, and sea ice dynamics.